2015
DOI: 10.3402/jom.v7.26250
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, genotype, and antibiotic susceptibility of Swedish and Thai oral isolates ofStaphylococcus aureus

Abstract: ObjectiveThe present study investigated phenotypes, virulence genotypes, and antibiotic susceptibility of oral Staphylococcus aureus strains in order to get more information on whether oral infections with this bacterium are associated with certain subtypes or related to an over-growth of the S. aureus variants normally found in the oral cavity of healthy carriers.Materials and methodsA total number of 157 S. aureus strains were investigated. Sixty-two strains were isolated from Swedish adults with oral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
17
0
2
Order By: Relevance
“…Staphylococcus aureus isolation rates differ considerably depending on the population. In healthy adults, oral carriage rates vary from 12 to 36%, with more frequent isolation (17–48%) among students 4 , 33 . The carriage rate documented in our study (18.5%) was similar as reported by other authors 34 – 36 , and remained within a typical range for European and American adult dental patients.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus isolation rates differ considerably depending on the population. In healthy adults, oral carriage rates vary from 12 to 36%, with more frequent isolation (17–48%) among students 4 , 33 . The carriage rate documented in our study (18.5%) was similar as reported by other authors 34 – 36 , and remained within a typical range for European and American adult dental patients.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies investigating the MRSA carriage rate among DHCPs, including dental students, the rate reported varied significantly from 0% to 21% ( Table ). At a glance, the rates obtained from the first two studies differed greatly from those in the remaining studies. The results obtained from the first two studies are close to the carriage rates observed during outbreaks of MRSA infection.…”
Section: Discussionmentioning
confidence: 51%
“…The mostly likely explanation is that those institutions were experiencing an outbreak of MRSA during the survey. The last four studies showed much lower rates, ranging from 0% to 3.2%. In particular, we reported that 3.1% of dental students in the same region had MRSA colonisation during a survey from December 2014 to January 2015.…”
Section: Discussionmentioning
confidence: 93%
“…Unfortunately, reports on these topics, for different countries, are not available and would require international multi-centre studies to further explain our data in relation to previous studies. Regardless of the local MRSA prevalence within DHCPs, surface disinfection is an important step to prevent spreading MRSA within the dental clinic [ 24 , 26 ]. No previous studies report on the prevalence of ESBL and VRE in dentistry, but the current data suggest that the prevalence is not elevated amongst dental students.…”
Section: Discussionmentioning
confidence: 99%